Diagnostics of oat plants by the method of laser interference auxanometry - Budagovskaya, Natalia; Guliaev, Valery (MTT, 2004)
The use of a new high sensitive method (accuracy 0.07 µm) laser interference auxanometry makes it possible to perform rapid diagnostics of oat plants at different growing conditions and selection of genotypes tolerant to stress. Oat plants cv. Horizont of sand and water cultures were used. The growth rate of plant leaves was measured by laser interference auxanometer with 10 sec or 1 min intervals during few hours every day. NaCl solution was added to the root zone to concentration 50 mM, 80 mM, 130 mM. In some experiments the roots were washed of NaCl with subsequent measurement of leaf growth rate. Antioxidant ambiol was added twice with one day interval to the root zone to concentration 1.7 µM. It was demonstrated that oat plants grown under deficiency of mineral nutrition had a low leaf growth rate. A significant increase was observed after single addition of antioxidant ambiol. In this case the leaf growth rate increased in two stages: rapid and a slower one. The leaf growth rate increased 4-fold when ambiol was added twice. Addition of NaCl to the root zone caused a two phase response reaction of plant leaves: decrease and the following increase in their growth rate. Secondary addition of NaCl led to a more significant decrease in leaf growth rate than at first addition of NaCl. The leaf growth restarted with low rate after less than 1 h during first phase. Restoration of leaf growth rate during the second phase at secondary and following additions of salt was partial (it did not achieve the initial level) and was more prolonged than at single addition of salt. The leaf growth rate increased at decrease in NaCl concentration at the root zone as result of addition of water or washing the roots of NaCl. At prolonged growing of oat plants at increased NaCl concentrations the yellowing and drying of the leaf ends was observed. The growth of this plant was suppressed as compared to control plants. Our results demonstrate the potentiality of laser interference auxanometry for evaluation of the changes in growth under different growing conditions.
Keywords: Ko; diagnostics; diagnostics; growth rate; oat plants